THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE AND ATTITUDE OF HYPERTENSIVE PATIENTS TOWARDS BLOOD PRESSURE CONTROL IN INPATIENT ROOM PATIENTS OF DR. ADJIDARMO HOSPITAL, LEBAK REGENCY IN 2023 - Fitriyeni, Yeni; Khamid, Abdul (HEARTY, 2025)
Background: Based on a preliminary study conducted at RSUD dr. Adjidarmo, Lebak Regency, it was found that as many as (90%) 18 out of 20 patients with hypertension claimed not to have made efforts to control blood pressure. Purpose: To determine the relationship between the level of knowledge and attitude with blood pressure control in hypertensive patients at RSUD dr. Adjidarmo Lebak Regency. Methods: Cross sectional through a point time approach where samples were taken using a total sampling of 58 respondents. Data analysis using chi square test. Results: Demonstrate the level of knowledge and attitude associated with blood control (p-value 0.022) and (p-value 0.002). Conclusion: There is a relationship between the level of knowledge and attitude and blood pressure control. It is expected that the hospital can provide information and health education regarding efforts to control blood pressure during hospital treatment and after hospitalization at home (discharge planning), so that blood pressure can be controlled properly and the impact of complications from hypertension can be avoided.